Added Value And Development Strategy Of Agroindustry Widoro Asih Instant Beverages In Ngliman Village, Sawahan District, Nganjuk Regency - Aji, Joni Murti Mulyo; Friska, Firadayana Laksmita (Universitas Garut, 2023)
Widoro Asih's instant herbal agro-industry business has the potential to be developed, because Widoro Asih's agro-industry has 20 kinds of products two of them instant tumeric herbal drink and tumeric dip pockets which have the benefit of not having sediment when it is brewing. The Widoro Asih’s agro-industry is one of the agroindustries that first created or innovated traditional herbal drink made from tumeric for sale in Nganjuk which are available in compact packaging, with a recipe preparedy by Mrs. Asih’s herself as the owner of the business. However, this business has not yet carried out detailed calculations to find out whether this business is feasible or not. The purpose of this study was to determine the amount of profit, added value of the Widoro Asih’s agro-industry and the right development strategy for the Widoro Asih’s agro-industry. Analysis of the data used is TR - TC Profits, added value using the Hayami method VA = NP - IC. In addition, using the SWOT analysis method to find out the right strategy to be applied in Widoro Asih's instant herbal agro-industry business. The results showed that Widoro Asih's instant herbal agro-industry business in Ngliman Village, Sawahan District, Nganjuk Regency could be said to be positive and profitable, and feasible to implement as evidenced by the results of data calculations. While the right business development strategy to implement is the SO strategy with strategic priorities being 1) Maintaining existing markets, 2) Creating new services such as membership or special delivery discos.